Makerspace network embeddedness, business model innovation, and user entrepreneurial performance in China: The moderating effect of environmental dynamics. - Jinbo Zhou; Weiren Cen; Yuzhi Ling (PLoS ONE)
Makerspaces gather a large number of entrepreneurial entities and resources, playing a vital role in the survival and development of user entrepreneurial enterprises. Based on network embeddedness theory and resource-based theory, this study employs hierarchical regression analysis and bootstrap method to examine the relationship between makerspace network embeddedness, business model innovation, and user entrepreneurial performance, as well as the moderating role of environmental dynamics. Using empirical data from 245 valid samples of user entrepreneurial firms in Chinese makerspaces, the results reveal that makerspace network embeddedness significantly promotes business model innovation and user entrepreneurial performance. Moreover, business model innovation has a significantly positive impact on user entrepreneurial performance, and partially mediates the relationship between makerspace network embeddedness and user entrepreneurial performance. Furthermore, environmental dynamics exhibit a significant positive moderating effect on the relationship between makerspace network embeddedness and business model innovation. These findings effectively reveal the mechanism for enhancing user entrepreneurial performance and offer practical insights for user entrepreneurial enterprises to leverage network embeddedness for improved entrepreneurial performance.